Co-valorization of lignin and waste polyethylene terephthalate (PET) via Fe/β-zeolite-catalyzed tandem depolymerization - Chang Li; Shihai Yang; Hongzhi Luo; Haiping Chen; Yishuang Wang; Yichen Chen; Chuannan Nie; Defang Liang; Mingqiang Chen (Chemical Engineering Journal, 2026)

A Process-based classification of meteorological mechanisms influencing airborne pollen concentrations in northern and northwestern China - Zining Yuan; Huiyu Ning; Xingqin An; Qingyu Wei; Defang Wei; Wenqiao Xue; Ning He; Lina Di; Xinli Yang; Ying Li; Rui Li; Hongjian Li; et al. (Atmospheric Research, 2026)

First Case of Nocardia seriolae Infection in China Cultured Channel Catfish ( Ictalurus punctatus ) - Mingqi Ai; Keyu Zhou; Qibin Jiang; Kun Peng; Yilin Wang; Yiteng Luo; Ping Ouyang; Defang Chen; Xiaoli Huang; Yi Geng (Journal of Fish Diseases, 2026)
Nocardia seriolae is a causative agent for fish skin ulcers and sarcoidosis, resulting in significant losses in both brackish and freshwater fish farming industries. From October to November 2023, channel catfishes ( Ictalurus punctatus ) cultured in Xiaowan reservoir at Dali city, Yunnan province in China, showed gross pathological changes with skin ulcers, white nodules in the liver and heart, histopathological tests revealed the typical granulomas and chronic hepatitis changes in the liver, and the clumps of filamentous bacteria in the heart and spleen. A Gram‐positive acid‐fast bacterium (CCF_NS01) was isolated from viscera (liver, spleen and kidney); biochemical tests and 16sRNA‐GyrB gene concatenated sequences analysis of this isolated microorganism identified it as N. seriolae . Drug sensitivity testing indicated susceptibility to commonly used antibiotics such as co‐trimoxazole, doxycycline, enrofloxacin, florfenicol, amikacin and rifampicin. In isolated CCF_NS01, multiple pathogenic factors corresponding to encoding genes were detected, including espG , mftF , pcaA , fadD32 , pks13 , narJ , feoB , sodA , katG and mceF . 100% mortality with 1 × 10 8 , 1 × 10 7 and 1 × 10 6 cfu/mL in a 35‐d challenge test period was observed, and the intraperitoneal injection median lethal dose (LD 50 ) was 1.89 × 10 4 cfu/mL. This is the first isolation report of N. seriolae infection from cultured channel catfish, aiming to warn against the continuous host‐range expansion of this pathogen, which is threatening the inland aquaculture industry.

Dendritic mesoporous silica nanospheres supported NiCo bimetallic catalysts for efficient cleavage of CC with formic acid for lignin depolymerization - Chang Li; Hongzhi Luo; Chunhui Zhou; Haiping Chen; Yishuang Wang; Shihai Yang; Chuannan Nie; Defang Liang; Mingqiang Chen (Chemical Engineering Journal, 2026)

Study on the correlation between Flavobacterium columnare infection and gill injury in Largemouth bass (Micropterus salmoides) and the protective effect of Enoxolone - Chen Li; Yunshan Qiu; Lin Luo; Xinnan Zhou; Hongli Liu; Ping Ouyang; Yi Geng; Defang Chen; Xiaoli Huang (Fish & Shellfish Immunology, 2025)

A lightweight model for plastic classification based on data augmentation - Jiachao Luo; Qunbiao Wu; Haifeng Fang; Jin Cao; Defang He (Journal of Cleaner Production, 2025)

Predicting soil organic carbon content using simulated insitu spectra and moisture correction algorithms in southern Xinjiang, China - Peimin Yang; Yu Wang; Bifeng Hu; Shuo Li; Songchao Chen; Defang Luo; Jie Peng (Geoderma Regional, 2024)

Chronic ammonia stress caused disorder of intestinal microbiota and damaged intestinal structure and function in yellow catfish (Pelteobagrus fulvidraco) - Lin Luo; Senyue Liu; Baipeng Chen; Fulong Li; Yongqiang Deng; Xiaoli Huang; Yi Geng; Ping Ouyang; Defang Chen (Aquaculture, 2024)

Comparative transcriptome and adaptive evolution analysis on the main liver and attaching liver of Pareuchiloglanis macrotrema - Qing Wu; Xiaoyang Zhang; Jie Li; Longjun Deng; Dongjie Wang; Min Liao; Zhonggang Guo; Xiaoli Huang; Defang Chen; Yan Wang; Shiyong Yang; Zongjun Du; et al. (Journal of Applied Genetics, 2022)

GSK3β inhibition suppresses the hepatic lipid accumulation in Schizothorax prenanti - Yan Wang; Xiaochen Zhan; Wei Luo; Liulan Zhao; Song Yang; Defang Chen; Zhiqiong Li; Linjie Wang (Fish Physiology and Biochemistry, 2019)

The rice “fruit-weight 2.2-like” gene family member OsFWL4 is involved in the translocation of cadmium from roots to shoots - Wentao Xiong; Peng Wang; Tianze Yan; Baobao Cao; Jun Xu; Defang Liu; Meizhong Luo (Planta, 2018)

Erratum to: CX3CR1 deficiency accelerates the development of retinopathy in a rodent model of type 1 diabetes - Eleni Beli; James M. Dominguez; Ping Hu; Jeffrey S. Thinschmidt; Sergio Caballero; Sergio Li Calzi; Defang Luo; Sumathi Shanmugam; Tatiana E. Salazar; Yaqian Duan; Michael E. Boulton; Susanna Mohr; et al. (Journal of Molecular Medicine, 2017)

CX3CR1 deficiency accelerates the development of retinopathy in a rodent model of type 1 diabetes - Eleni Beli; James M. Dominguez; Ping Hu; Jeffrey S. Thinschmidt; Sergio Caballero; Sergio Li Calzi; Defang Luo; Sumathi Shanmugam; Tatiana E. Salazar; Yaqian Duan; Michael E. Boulton; Susanna Mohr; et al. (Journal of Molecular Medicine, 2016)

Acute Toxicity and Genotoxicity of Carbendazim, Main Impurities and Metabolite to Earthworms (Eisenia foetida) - Zhibo Huan; Jinhui Luo; Zhi Xu; Defang Xie (Bulletin of Environmental Contamination and Toxicology, 2016)

Residues, dissipation, and risk assessment of spinosad in cowpea under open field conditions - Zhibo Huan; Jinhui Luo; Zhi Xu; Defang Xie (Environmental Monitoring and Assessment, 2015)

Dissipation and Residues of Difenoconazole and Azoxystrobin in Bananas and Soil in Two Agro-Climatic Zones of China - Zhibo Huan; Zhi Xu; Daizhu Lv; Defang Xie; Jinhui Luo (Bulletin of Environmental Contamination and Toxicology, 2013)